(untitled) (Indian Journal of Arid Horticulture, 2021)
Immense prospects exist to develop desirable cultivars of annonaceous fruits by conventional breeding techniques. There is greater scope to exploit inter-specific variation than intra-species variation. Edible Annona species exhibit morphological affinity to one another but each one is unique and distinct for fruit shape, size, skin surface, pulp colour, texture, flavour and taste. Some species like Annona squamosa exhibit narrow genetic variation. However, several interesting traits are available in one or the other allied Annona species. Because thereare no serious barriers in inter-specific hybridization between A. squamosa, A.cherimola and A.reticulata gene transfer across species boundaries is possible. Gene exchange among them should result in interesting novel recombinants at times most esteemed ones like the popular atemoya.